Contextualising degree-level achievement: an exploration of interactions between gender, ethnicity, socio-economic status and school type at one large UK university. Issue 4 (2nd October 2017) - Jones, Steven; Pampaka, Maria; Swain, Daniel; Skyrme, Julian
Abstract: Differentials in UK degree outcomes have been noted for some time, with research showing that not all types of students enjoy comparable levels of attainment, even when prior qualifications are controlled for. This article offers a new perspective by using regression models to examine interactions between the key variables that predict success among around 9000 students at one major UK university in terms of their chances of obtaining a 'good' (upper second or better) degree and a 'first' degree. As in previous studies, gender is found to be significantly influential, with female students' attainment being superior to that of male students. However, significant interactions are noted between gender, ethnicity and socio-economic class indicators. These interactions are integral to developing a better understanding of what happens to equal-attainment students once they reach university, and they allow for a more fine-grained and accurate picture to emerge of the different factors that influence success. We interpret these interactions, along with school type effects, and discuss their potential implications for the ways in which university applicants are selected and university students are taught.